Molecular Cytogenetic Study in Patients with Acute Lymphoblastic Leukemia (ALL) in Erbil Province - Heveen Omar Hassan; Nadhum Jalal Esmael (Zanco Journal of Pure and Applied Sciences, 2021)
Background: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children and is also important in older adults. Chromosome number or structure abnormalities are seen in approximately 90% of children and 70% of adult patients with ALL. The aim of this study was to determine the prevalence of these chromosomal abnormalities in ALL patients using Fluorescence in situ Hybridization (FISH) technique and to define the frequency of chromosomal abnormalities of ALL patients in adults and children in Erbil Province. Methods: In this cross-sectional study, we evaluated karyotype results in blood samples, that collected from 55 patients with ALL (in both sexes) in Nanakali Hospital in Erbil Province. Thirty healthy individuals were selected as the control group. Patients ages ranged between 1 to 63 years old. The samples were centrifuged to extract nucleated cells. The cells were then subjected to hypotonic shock, fixed with methanol and acetic acid. A cell suspension was then prepared for FISH technique. After examining the samples with fluorescent microscope, the obtained data along with demographic and baseline characteristics of patients were entered in SPSS software, then statistically analyzed. Results: The prevalence of chromosomal abnormalities among ALL group was 52.7% (n = 29). Of these, 31¬% (9 people) had abnormalities in chromosome number and 69¬% (20 people) had abnormalities in chromosome structure. The most common chromosomal abnormality was translocation t (9; 22), which accounted for 31¬% of all abnormalities and its prevalence among ALL patients was 16.4¬%. Clonal trisomy and t (12; 21) also accounted for 13.8% and 10.3% of abnormalities, respectively. Clonal trisomy was the most common abnormality in chromosome number, accounting for 44.4% (n = 4) of abnormalities. Only one patient with single chromosome X (X0) pattern was observed in patients. There was no significant (P> 0.05) relationship between the incidence of chromosomal abnormalities with gender, family history, history of surgery and bacterial infection, occupation, place of residence, smoking and blood type as stated from the questionnaire form. Conclusion In the current study, concluded that at least one chromosomal abnormality was found in more than half of all patients with ALL. Structural abnormalities were more common than chromosome number abnormalities. Awareness of the magnitude of the problem demands implementation of preventive, diagnostic and therapeutic strategies for leukemia’s in the Kurdistan region as well as planning epidemiologic studies and research programs.